Effect of ultra-endurance exercise on left ventricular performance and plasma cytokines in healthy trained men - Krzemiński, K; Buraczewska, M; Miśkiewicz, Z; Dąbrowski, J; Steczkowska, M; Kozacz, A; Ziemba, A (Biology of Sport, 2016)
The purpose of this study was to investigate the effect of ultra-endurance exercise on left ventricular (LV) performance and plasma concentration of interleukin (IL)-6, IL-10, IL-18 and tumour necrosis factoralpha (TNF-IX) as well as to examine the relationships between exercise-induced changes in plasma cytokines and those in echocardiographic indices of LV function in ultra-marathon runners. Nine healthy trained men (mean age 3011.0 years) participated in a 100-km ultra-marathon. Heart rate, blood pressure, ejection fraction (EF), fractional shortening (FS), ratio of early (E) to late (A) mitral inﬂow peak velocities (E/A), ratio of early (E') to late (A') diastolic mitral annulus peak velocities (E‘/A’) and E-wave deceleration time (DT) were obtained by echocardiography before, immediately after and in the 90th minute of the recovery period. Blood samples were taken before each echocardiographic evaluation. The ultra-endurance exercise caused significant increases in plasma IL-6, IL-10, IL-18 and TNF-α. Echocardiography revealed signiﬁcant decreases in both E and the E/A ratio immediately after exercise, without any significant changes in EF, FS, DT or the E/E’ ratio. At the 90th minute of the recovery period, plasma TNF-or and the E/A ratio did not differ significantly from the pre-exercise values, whereas FS was significantly lower than before and immediately after exercise. The increases in plasma TNF-or correlated with changes in FS (r=0.73) and DT (r=-0.73). It is concluded that ultra-endurance exercise causes alterations in LV diastolic function. The present data suggest that TNF-or might be involved in this effect.